Rubén Hernández-León: Metropolitan Migrants. The Migration of Urban Mexicans to the United States.: University of California Press, Berkeley 2008, 258 s. - Pařízková, Alena (Lidé města, 2009)
A review of the book by Rubén Hernández-León.